Evaluasi Pencahayaan Buatan terhadap Kenyamanan Visual Pengguna pada Ruang Baca Gedung DPK Kalimantan Timur - Paramita Waluyo; Ayu Asvitasari; Mafazah Noviana (Universitas Sebelas Maret Surakarta, 2025)
Evaluation of Artificial Lighting on User Visual Comfort in DPK Kalimatan Timur Building Reading RoomsThis study evaluates the artificial lighting levels in the Children’s and Digital Reading Rooms of DPK Kaltim to assess their compliance with the SNI 6197:2020 and suitability for user visual comfort. Using a descriptive quantitative approach, illumination levels were measured with a lux meter and simulated using Dialux software. The results revealed significant non-compliance with the standards. The Children's Reading Room recorded an average of 107.3 lux (measured) and 269 lux (simulated), far below the 350 lux standard. Similarly, the Digital Reading Room measured 78.1 lux (measured) and 251 lux (simulated), failing to meet the required 500 lux. These deficiencies severely compromise user comfort and visual performance. Therefore, this study recommends a lighting system redesign, proposing the installation of 20 units lamps in the Children’s Reading Room and 24 units in the Digital Reading Room of 40 Watt LED Slimbend Recessed to achieve the required illumination standards.